PENERAPAN PERATURAN PEMERINTAH NOMOR 53 TAHUN 2010 TENTANG DISIPLIN PEGAWAI NEGERI SIPIL DALAM PENYELESAIAN PELANGGARAN DISIPLIN OLEH PEGAWAI NEGERI SIPIL DI KOTA JAMBI - , Refialdi Made Suci, SH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was intended to identify (1) determination of Government Regulation Number 53 year 2010 about civil servant discipline in Jambi Municipality, (2) obstacle faced in implementation of the regulation over discipline violation by civil servant in Jambi and (3) formulate juridical steps done to create good civil servant in Jambi. This was empirical research that was conducted by identifying and clarifying implementation of laws (field study). It was also normative study that analyzed various laws related to civil servant discipline (literary study). Field study was conducted by interviewing informants and officials in Jambi regional personnel agency (BKN) and questionnaire with respondent of civil servant in Jambi. Result of the research indicated that : Government Regulation No 53 year 2010 about Civil Servant Discipline in Jambi have not been implemented effectively. Obstacle impeding implementation of the government regulation in Jambi include juridical obstacle of laws system and ineffective monitoring. In addition, there was also technical obstacles of no Jambi regional regulation that specially govern provision of certain firm punishment in Jambi. Action that can be done to create good civil servant in Jambi is reviewing regulation that is guidance in discipline enforcement and increase monitoring on civil servant in Jambi. Moreover, local regulation as guidance in discipline enforcement of civil servant in Jambi and giving discipline sanction in Jambi should be made.